1966
DOI: 10.1126/science.154.3753.1202
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Sister Chromatids in Mammalian Cells

Abstract: Segregation of sister chromatids in embryonic mouse cells in primary tissue culture is not random. In mitosis those chromatids replicated on a DNA template synthesized during the preceding division cycle are separated from those constructed on a template synthesized two division cycles previously. Segregation in cells of the Chinese hamster follows a similar, but less pronounced, pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0
1

Year Published

1971
1971
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 14 publications
0
68
0
1
Order By: Relevance
“…It was proposed that stem cells might always inherit template-containing DNA strands allowing them to escape cancer-causing mutations. In support of the genome-wide directedsegregation mechanism, nonrandom segregation of sister chromatids was observed in some studies that followed the distribution of bromo-deoxyuridine-or radio-labeled chromosomes (Lark et al 1966;Rosenberger and Kessel 1968;Potten et al 1978;Merok et al 2002;Smith 2005), while the random pattern was found in other studies (Ito and McGhee 1987;Yadlapalli et al 2011). Another interesting case of selective segregation of chromatids of only the paternal set of chromosomes in the apical cells of shoots and roots of the water fern Marsilea vestita has been reported (Tourte et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that stem cells might always inherit template-containing DNA strands allowing them to escape cancer-causing mutations. In support of the genome-wide directedsegregation mechanism, nonrandom segregation of sister chromatids was observed in some studies that followed the distribution of bromo-deoxyuridine-or radio-labeled chromosomes (Lark et al 1966;Rosenberger and Kessel 1968;Potten et al 1978;Merok et al 2002;Smith 2005), while the random pattern was found in other studies (Ito and McGhee 1987;Yadlapalli et al 2011). Another interesting case of selective segregation of chromatids of only the paternal set of chromosomes in the apical cells of shoots and roots of the water fern Marsilea vestita has been reported (Tourte et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Conservation of immortal strands was observed first in embryonic cells (16), and its main role may be in the opportunities it provides for strand-specific control of differentiation. But the present analysis is limited to showing that strand conservation in somatic stem cells gives us a simple explanation for the strange relation between dose and time in the production of mutant clones, in particular the production of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In 1975, John Cairns (Cairns 1975), based on previous reports of non-random segregation of sister chromatids in mammalian cells (Lark et al 1966), proposed the "immortal strand" hypothesis according to which stem cells would retain template DNA strands, whereas newly synthesized DNA replicas would segregate into differentiating daughter cells. By keeping template strands, stem cells would avoid the accumulation of mutations that could occur during DNA replication.…”
Section: Introductionmentioning
confidence: 99%